STUDY PELAKSANAAN PENGENDAUAN TIKUS OJ PELABUHAN TANJUNG TEMBAGA KOTA PROBOUNGGO TAHUN 2014 - Merina Dea Haruni; Setiawan .; Hadi Suryono (GEMA LINGKUNGAN KESEHATAN, 2014)
Rat is a a type of rodents. One of their characteristics is that their teeth continue to grow so theyneed to gnaw objects in their surroundings. Rats are harmful in terms of economic, health, aesthetics andpublic services. A Report on rat control carried out in port health office (KKP) of Probolinggo in 2013showed that 35 rats were successfully trapped. The Ministry of Health Decree No. 431/2007 stated thatthe KKP must the make every effort to eliminate rats from KKP area. The purpose of this research was tolearn the rat control being implemented in Tanjung Tembaga Port of Probolinggo in 2014.This was a non-experimental study where data were analyzed descriptively by describing the ratcontrol activity performed by the KKP Probolinggo. Rat control was carried out in accordance with Ministerof Health decree No. 431/MENKES/SK/IV/2007. Various data were collected through observation,interviews, installation of rat traps; identification of rats and fleas found on them.The results showed that of among the five variables being investigated, four variables associatedwith rat control activities have not met the designated requirements, and only one variable: ratinspection/identification has satisfied the requirement. The variables that have not met the requirementsinciuded mapping, work schedules, rat proofing observation, and rat trap installation procedures. Mappingand work schedule failed to describe the locations where rat traps were placed. Rat proofing observationwas not conducted regularly and procedures in deploying rat traps were done not in accordance with theMinister of Health decree No. 431/MENKES/SK/IV/2007.It can therefore be concluded that rat control program in Tanjung Tembaga port of Probolinggo in2014 has not satisfied the desiqnated requirements. It was recommended that KKP Probolinggo improveits rat control program with respect to the said decree. Mapping should be enhanced by specifyinglocations of garbage bins, sewer system, and stockpile places in open areas. The work schedule shouldspecify locations of rat control, provide counseling time warehouse/building operators, lists of equipmentand materials required. Rat proofing should be observed regularly. Rat traps should be installed onevenings and the removal should be done in the mornings betore daily activities in full swing, and trapswith captured rats should be labeled accordingly.